Sistem Penunjang Keputusan Penilaian Pegawai Menggunakan Analytical Hierarchy Process - Arrizky Rahmat Alifiansyah; Siti Aminah; Bagus Kristomoyo Kristanto (J-INTECH ( Journal of Information and Technology), 2022)
There are many divisions in work. Each division has different targets. The company also has an assessment of its employees which is carried out by HRD. HRD as a person who manages staffing has a lot of work, while the assessment of a company is still done manually so that HRD has difficulty monitoring and assessing its employees. This is important for companies to maintain the quality of their workers. The purpose of this research is to create a decision support system that helps HRD in assessing its employees. The system must include features used to assess employees and process the calculations automatically. So that the decision support system will be designed using the AHP method and KPI indicators. The system can perform calculations using AHP and can show the calculation results in ranking order.